Démarche collaborative entre praticiens et chercheurs en recherche pédagogique : l'exemple de la structuration d'une filière de pédagogie coopérative dans un collège en Normandie - Laurent Lescouarch (Université de Provence, 2020)
This article looks at the conditions for conducting pedagogical research on the development of cooperative pedagogical practices in secondary schools in France. It analyses the conditions of the collaborative dynamics between practitioners and researchers in a perspective of pedagogical change by highlighting the tensions inherent in these forms of research. The contribution highlights the internal dynamics of the team in this project and the functions and postures of the researcher to foster commitment and the dimensions to be taken into account in this type of support. From this contextualized situation, it also questions the gaps between the theoretical organization models of collaborative research and the actual logics of working with teams.